Role of oxygen‐vacancy in piezoelectric properties and fatigue behavior of (Bi0.5Na0.5)0.93Ba0.07Ti1+xO3 ceramics. Issue 9 (2nd March 2019) - Jia, Xuanrui; Zhang, Jingji; Wang, Lejian; Wang, Jiangying; Du, Huiwei; Yao, Yaxuan; Ren, Lingling; Wen, Fei; Zheng, Peng
Abstract: In this reported study, (Bi0.5 Na0.5 )0.93 Ba0.07 Ti1+ x O3 (abbreviated as BNBT1+ x ) ceramics, containing Ti‐nonstoichiometry that ranged from a 2% deficiency to a 1% excess, were designed and systematically characterized. The results of the X‐ray diffraction Rietveld refinement and X‐ray photoelectron spectroscopy analysis of these materials revealed that the amount of Ti in the BNBT1+ x ceramics significantly affected the degree of coexistent rhombohedral/tetragonal phases and also affected the content of singly/doubly charged oxygen‐vacancy ( V O · / V O · · ) in the ceramics. After poling and 10 5 fatigue cycles, the variation in Raman resonance line‐width of the Ti–O bond in the BNBT1+ x ceramics was found to be strongly dependent on the amount of Ti in the ceramic. The T i T i 4 + ( 3 + ) ′ - V O · → T i T i 4 + ( 3 + ) ′ - V O · · transformation and clustering of the T i T i 4 + ( 3 + ) ′ - V O · · defects under electrical loading were considered to be a critical factor in electric field‐induced structural transition and fatigue properties of the material. Abstract : Although high TF‐R /Td of ~160oC was detected in BNBT1+x ceramics with whether Ti excess or high Ti deficiency, high electric conductivity with ~1 eV and significant degradation in Smax and d33* max after 105 electrical loading were found, probable due to large amounts of incipient defects.